Effects of polyethylene film wrap on cooler shrink and the microbial status of beef carcasses - Sampaio, Guilherme S. L.; Pflanzer-Junior, Sergio B.; Roca, Roberto De O. [UNESP]; Casagrande, Leandro; Bedeschi, Elaine A.; Padovani, Carlos Roberto [UNESP]; Miguel, Giulianna Z. [UNESP]; Santos, Carolina T. [UNESP]; Girao, Lucio V. C.; Miranda, Zander B.; Franco, Robson M. (Elsevier B.V., 2015)
The present study evaluated the use of polyethylene film wrapping of beef half carcasses and its effects on cooler shrink, cooling characteristics and microbial status of the half carcasses. Film wrapping reduced cooler shrink by 55.2%, 43.1%, 36.0% and 30% after 24, 48, 72 and 96 h of cooling, respectively, compared to the unwrapped half carcasses, whereas the surface water activity showed no significant differences among the time periods. The wrapped half carcasses had a lower cooling rate and higher surface and internal temperatures. The highest values of the aerobic mesophiles, Staphylococcus aureus and Enterobacteriaceae were found in the half carcasses wrapped in film. No significant differences were found in the values of Escherichia con. The polyethylene film was effective in reducing cooler shrink; however, it caused a delay in cooling, thereby enabling greater microbial occurrences and counts and impairing the hygienic and sanitary conditions of the carcasses, which may be an impediment to the practical application of this technology. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Bos indicus; Carcass chilling; Plastic film covering; Weight loss; Hygiene indicators; Petrifilm